Patient perspective on barriers in type 2 diabetes self‐management: A qualitative study - Justin Tuobenyiere; Gwendolyn Patience Mensah; Kwadwo Ameyaw Korsah (Wiley, 2023)
Abstract Aim To explore the perceived barriers in Type 2 Diabetes care among patients with diabetes. Design The study adopted a qualitative exploratory‐descriptive design. Methods A semi‐structured interview guide was used to collect data from fifteen (15) purposively sampled patients with Type 2 Diabetes at a primary level health facility in the Bono East region. Participants' ages ranged between 42-72 years. The interviews were audio‐recorded, transcribed verbatim and analysed using thematic content analysis. Results Patients with Type 2 Diabetes encountered a range of barriers in diabetes care. These barriers included lack of knowledge of diabetes dietary management strategies, financial constraints, non‐compliance to treatment, lack of glucometers, lack of social support, and increased waiting time at health care facilities. The findings indicate that more education on diabetes and dietary management is required as well as social support from peers, family, and non‐governmental organizations. Patient or public contribution Diabetes self‐management barriers as revealed by the patients who were participants of this study requires nurses and midwives to ensure that self‐management education is well understood by patients and their relatives. This would empower the patients and bring clarity to their confusion about self‐care practices.